PENGEMBANGAN KURIKULUM DI INDONESIA - Hutajulu, Maria Margaeta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Curriculum development is a crucial element in the education system aimed at ensuring the relevance and quality of education. In Indonesia, the curriculum undergoes continuous evolution to adapt to the changing times and societal needs. This research aims to examine the curriculum development process in Indonesia, the challenges faced, and its implications for educational practices. This study employs a qualitative method with a document analysis and literature review approach. Data were collected from various secondary sources, including official curriculum documents, academic articles, and education policy reports. Analysis was conducted to identify trends, challenges, and successes in curriculum development in Indonesia. The findings indicate that curriculum development in Indonesia involves various factors, including local needs and international standards. Challenges include limited resources and insufficient training for teachers. This research provides recommendations for improving the curriculum development process to be more effective and aligned with Indonesia's educational needs.